Die Bedeutung von Gütezeichen und Herkunftsangaben beim Rindfleischkauf: Ergebnisse einer repräsentativen Verbraucherstudie in Bayern; The Relevance of Certification Marks and Geographical Indications when buying Beef - Results of a Representative Consumer Study in Bavaria - Adriano Profeta; Richard Balling; Sabine Will (German Journal of Agricultural Economics (GJAE), 2011)
– While for the time period 1995 to 1998 significant and positive welfare effects and a consumer willingness-to-pay could be measured for the origin and certification mark "Qualitaẗ aus Bayern" there is a new situation after the BSE crisis due to changes of several impact factors. In the framework of this paper we analyze if certification marks still have relevance when buying beef. For this purpose we conduct an empirical consumer study in Bavaria. At this we focus on the label "Gepruf̈te Qualitaẗ Bayern", the denomination Bavarian Beef which is meanwhile registered as protected geographical indication (PGI) according to regulation (EC) 510/06 and the label "Qualitaẗ und Sicherheit" (QS). The results show significant but varying effects for all analyzed labellings.
Keywords: 330; Rindfleisch; Produktinformation; Konsumentenverhalten; Bayern